Analisis Tenaga Kerja, Modal dan Luas Lahan Terhadap Hasil Produksi Usaha Tani Padi di Desa Batarang Kecamatan Kusan Tengah Kabupaten Tanah Bumbu - Nur sidratun Nissa, Nissa; Wardhana, Ali (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
This study examines the influence of the aplication effect of labor, capital and land area on the production of rice farming in Batarang Village, Kusan Tengah Subdistrict. The method in this research used a quantitative method and interviews with total 58 respondent of farmers in Batarang Village, Kusan Tengah District. Processing data using multiple linear regression analysis with Eviews. The results showed that the labor variable (X1) has a positive and insignificant effect, the capital variable (X2) has a positive and not significant effect, the land area variable (X3) has a positive and significant effect on the production of  farmers in Batarang Village, Kusan Tengah Subistrict.